Liraglutide Increases VEGF Expression via CNPY2-PERK Pathway Induced by Hypoxia/Reoxygenation Injury - Chong Liu; Chong Liu; Yong Liu; Jing He; Rong Mu; Yanbo Di; Na Shen; Xuan Liu; Xiao Gao; Jinhui Wang; Tie Chen; Tao Fang; et al. (Frontiers Media S.A., 2019)
Liraglutide (Lir) is a glucagon-like peptide-1 receptor agonist that lowers blood sugar and reduces myocardial infarct size by improving endothelial cell function. However, its mechanism has not yet been clarified. Unfolded protein response (UPR) plays an important role in the pathogenesis of myocardial ischemia-reperfusion injury. It determines the survival of cells. Endoplasmic reticulum position protein homologue 2 (CNPY2) is a novel initiator of UPR that also participates in angiogenesis. To this extent, the current study further explored whether Lir regulates angiogenesis through CNPY2. In our article, a hypoxia/reoxygenation (H/R) injury model of human umbilical vein endothelial cells (HUVECs) was established and the effect of Lir on HUVECs was first evaluated by the Cell Counting Kit-8. Endothelial tube formation was used to analyze the ability of Lir to induce angiogenesis. Subsequently, the effect of Lir on the concentrations of hypoxia-inducible factor 1α (HIF1α), vascular endothelial growth factor (VEGF), and CNPY2 was detected by enzyme-linked immunosorbent assay. To assess whether Lir regulates angiogenesis through the CNPY2-initiated UPR pathway, the expression of UPR-related pathway proteins (CNPY2, GRP78, PERK, and ATF4) and angiogenic proteins (HIF1α and VEGF) was detected by reverse transcription-polymerase chain reaction and Western blot. The results confirmed that Lir significantly increased the expression of HIF1α and VEGF as well as the expression of CNPY2-PERK pathway proteins in HUVECs after H/R injury. To further validate the experimental results, we introduced the PERK inhibitor GSK2606414. GSK2606414 was able to significantly decrease both the mRNA and protein expression of ATF4, HIF1α, and VEGF in vascular endothelial cells after H/R injury. The effect of Lir was also inhibited using GSK2606414. Therefore, our study suggested that the CNPY2-PERK pathway was involved in the mechanism of VEGF expression after H/R injury in HUVECs. Lir increased the expression of VEGF through the CNPY2-PERK pathway, which may promote endothelial cell angiogenesis and protect HUVEC from H/R damage.